(3GdeNQhWGJs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3Cf ehbY Yde eG jbY ai GdeNWQhWGJ ef GdbWhY heG JYQV ajgG ef GdCTcGd hGdNWhW ef Yde GdgfOSI s
(3BNQgG (B:s
(3hPdc eG dGjecf abWY ai CcKQ ef ehVYjf hPdc eG CQOfG ai gPG GdcJGH s
(3HgG CTcGd gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B323 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1456s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B- (3eTgO (B(164) s
Keywords: (3GdQjGVjGJs